Implementation of Service Based Business Model Application in Tobacco Products Industrial Area Management in Sumenep Regency - Rahman, Hairul; Sa'adah, Siti; Safitri, Dewi Bela (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2024)
The main problem in this study is the effectiveness of implementing the Service-Based Business Model (MBBL) in KIHT management in Sumenep Regency. The successful implementation of this model is expected to maximize the performance of KIHT management by KIHT organizers, considering that the purpose of KIHT development is to improve excise supervision (reducing the circulation of non-excise cigarettes) and improve the regional economy. This study uses a qualitative method with data collection techniques through (1) Focus Group Discussions (FGD), (2) observation, and (3) interviews with Cigarette Entrepreneurs (PR) to be able to adjust the services needed in MBBL. Based on observations that have been made using the three research methods mentioned, the Service-Based Business Model (MBBL) in KIHT management in Sumenep Regency, KIHT organizers must provide basic services through the formation of four divisions, namely: (1) Finance and Risk Management Division, (2) HR and Personnel Division, (3) Operational and Service Development Division, and (4) Development Division (Building & Property Management).